Safety culture in the operating room: translation, validation of the safety attitudes questionnaire – operating room version - Teodor Pevec; Tit Albreht; Eva Turk (BMC Health Services Research, 2023)
Abstract Background Measuring the safety culture in Healthcare is an important step in improving patient safety. One of the most commonly used instruments to measure the safety climate is the Safety Attitudes Questionnaire (SAQ). The aim of the current study was to establish the validity and reliability of the Slovenian version of the SAQ for the operating room SAQ-OR. Methods The SAQ, consisting of six dimensions, was translated and adapted to the Slovenian context and applied in operating rooms from seven out of ten Slovenian regional hospitals. Cronbach’s alpha and confirmatory factor analysis (CFA) was used to evaluate the reliability and validity of the instrument. Results The sample consisted of 243 health care professionals who hold positions in the OR, divided into 4 distinct professional classes, namely, 76 surgeons (31%), 15 anesthesiologists (6%), 140 nurses (58%) and 12 auxiliary persons (5%). It was observed a very good Cronbach's alpha (0.77 to 0.88). The CFA and its goodness-of-fit indices (CFI 0.912, TLI 0.900, RMSE 0.056, SRMR 0.056) showed an acceptable model fit. There are 28 items in the final model. Conclusions The Slovenian version of the SAQ-OR revealed good psychometric properties for studying the organisational safety culture.